Effect of Enalapril on erythropoiesis recovery in murine anemia - VEUTHEY, TV; D´ANNA, MC; SÁNCHEZ, M; GATTI, CJ; ROQUE, ME (Ars Pharmaceutica (Internet), 2008)
The presence of Angiotensin receptors in erythropoietic bone marrow and marrow stromal cells clearly shows a mechanism forRennin-Angiotensin System-mediated regulation of erythropoiesis. The aim was to study the effects of Angiotensin-ConvertingEnzyme inhibition (ACEI) as Enalapril(E) on erythropoietic response in anemic mice treated with Phenylhydrazine (PHZ) bymeans of hematological and histological studies. Both PHZ and E-PHZ-treated mice showed hemolysis on day 14. Howeverthe restoration of anemic state occurred on day 16 in PHZ-treated mice and on day 20 in E-PHZ-treated mice. Erythropoieticactivity was observed in spleen (day16) and kidney (day20) of E-PHZ-treated mice. In PHZ-treated mice erythropoietic activitywas seen in spleen and kidney on day 16. We conclude that Inhibition of ACE with Enalapril delays the erythropoietic recoveryof hemolytic anemia in E-PHZ-treated mice. Erythropoietic activity in spleen and kidney suggest an involvement of theseorgans in the erythron recovery.